Mechanistic insight into the aerobic oxidation of benzyl alcohol catalyzed by the CuII–TEMPO catalyst in alkaline water solution. Issue 102 (5th October 2015) - Duan, R. F.; Cheng, L.; Zhang, Q. C.; Ma, L. S.; Ma, H. Y.; Yang, J. C.
Abstract : The benzyl alcohol oxidation to benzaldehyde in the alkaline water solution catalyzed by Cu II /L–TEMPO catalyst is investigated by density functional method. The favorable mechanisms and the role for the water ​have also been predicted. Abstract : Density functional theory (DFT) calculations have been performed to investigate the benzyl alcohol oxidation to acetaldehyde by a Cu II /L–TEMPO (L: bis[2- N -(4-fluorophenyl)-pyrrolylcarbaldimide]) catalyst system in alkaline water solution. The catalytic cycle consists of catalyst activation, substrate oxidation and catalyst regeneration parts. Four pathways (path A, path B, path C and path D) for the catalyst activation step are considered. The rate-determining steps are proton transfer in these pathways. Moreover, water participation plays a major role in the proton transfer step. In consideration of the high concentration of the solvent water, path C and path D are supposed to be competitive during the reaction, with path D more favourable.